Migrating Scholars and Ideas The Prague School and Scandinavia - Beke, Márton (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2011)
The Prague Linguistic Circle was founded over 80 years ago. Its merit is to define the language as a structure, as well as structuralism as a method of research, which continues to be the most important theory of linguistic, literary and aesthetic. The author focuses on the history of structuralism in Scandinavia and its impact on Europe and the United States in the interwar period and during the Second World War, as well as describes the Czech structuralism in Scandinavia after World War II. The key figure in the relationship between the Prague school of structural linguistics and Nordic is undeniably Roman Jakobson. His influence – as well as his colleagues – is most evident in the case of Danish scholars and Linguistic Circle of Copenhagen. But there he argues that the Czech structuralism and functional linguistics dominate the Scandinavian linguistics to the present day, although in some cases, their influence continues to give noticeable results of research.
Keywords: Czech linguistic; Scandinavian linguistic; Prague linguistic circle; Roman Jakobson